The quiet revolution in Saudi-Israeli relations. Issue 2 (15th March 2021) - Rynhold, Jonathan; Yaari, Michal
ABSTRACT: This article charts the development of a quiet revolution in Israeli-Saudi relations, based on a wide variety of sources including interviews with senior Israeli and American officials and background conversations with Arab diplomats. The underlying cause of this revolution has been the dramatic increase in the threat posed by Iran, which has led to unprecedented strategic cooperation. For the first time, the Saudi regime has sanctioned steps towards normalizing relations with Israel prior to a comprehensive peace agreement. Of primary importance has been Israel's willingness and ability to assist in countering Iran, and the lack of reliable and effective alternative means available to Saudi Arabia in this regard. At the same time, domestic politics in Israel – combined with the Saudi regime's sensitivity to the transnational resonance of the Palestinian issue – continue to constrain the relationship. Consequently, without major progress towards a resolution of the conflict and Palestinian statehood, the full normalization of Saudi-Israeli relations is highly unlikely.